2017
DOI: 10.21831/jpai.v15i2.17215
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan, Lingkungan Kerja, Budaya Organisasi, Motivasi Kerja Dan Locus of Control Terhadap Kinerja Individu Pada Umkm Di Kota Padang

Abstract: UMKM sangat berpengaruh pada perekonomian masyarakat. Berbagai upaya dilakukan pemerintah agar seluruh masyarakat memiliki penghasilan dan kalau memungkinkan memiliki usaha sendiri, seperti pelatihan, pembinaan dan pendampingan. Tetapi usaha tersebut tidak menjamin UMKM semakin meningkat, baik dari segi kuantitas maupun dari segi kualitas. Karena Jumlah penduduk menganggur di Sumatra Barat bertambah 12.800 orang dalam satu tahun belakangan, sejak 2016 hingga 2017. Padahal jika UMKM berkembang akan mempengaruhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…So, it can be concluded that the value of p and the value of α = 0.05, it can be seen that the significance value is p (0,000)> α = 0.05, which means that simultaneously the variables of organizational culture, business partnerships, and motivation have an effect on the performance of MSEs in Sleman. This research is supported by previous research conducted by (Helmawati et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…So, it can be concluded that the value of p and the value of α = 0.05, it can be seen that the significance value is p (0,000)> α = 0.05, which means that simultaneously the variables of organizational culture, business partnerships, and motivation have an effect on the performance of MSEs in Sleman. This research is supported by previous research conducted by (Helmawati et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…According to (Helmawati et al, 2017) in the research results show that organizational culture and motivation partially and simultaneously have a positive and significant effect on performance, good organizational culture can be applied by companies and motivation continues to be improved so that individual performance will increase. H4: Simultaneously organizational culture, business partnerships, and motivation have a positive and significant effect on the performance of micro and small business actors in Sleman Regency.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Upaya yang dilakukan untuk mempertahankan karakteristik wirausaha yang ditentukan oleh faktor internal seperti locus of control" (Liñán et al, 2008)', (Lüthje & Franke, 2003, (Shane et al, 2003) merupakan kepribadian pemilik usaha dimana mereka yakin dapat meningkatkan kinerja UMKM. (Helmawati et al, 2017) mengatakan kinerja UMKM tergantung pada bagus tidaknya kinerja individu pemilik usaha, salah satu faktornya adalah locus of control. Setiap pemilik usaha yang siap menanggung risiko menunjukkan kinerja guna menghadapi pasar (Lüthje & Franke, 2003)," (Yusof et al, 2007).…”
Section: Pengaruh Karakteristik Wirausaha Terhadap Kinerja Umkmunclassified
“…Efforts made to maintain entrepreneurial characteristics are determined by internal factors such as locus of control (Renaldo, Sudarno, & Hutahuruk, 2020b), (Liñán et al, 2008), (Lüthje & Franke, 2003), (Shane et al, 2003) is the personality of business owners where they believe they can improve the performance of MSMEs. (Helmawati et al, 2017) said that the performance of MSMEs depends on whether the performance of individual business owners is good or not, one of the factors is locus of control. Every business owner who is ready to take risks shows performance to face the market (Lüthje & Franke, 2003), (Yusof et al, 2007).…”
Section: Discussionmentioning
confidence: 99%